Editorial Vol14 no1 - Graham Connelly (Scottish Journal of Residential Child Care)
Mood-changing power is the theme of the moment. Earlier this month – on 1 April 2015 – most of the provisions of the Children and Young People (Scotland) Act 2014 became law. While the Act has provisions which affect all children in Scotland, including the requirement for a 'named person' to provide a single point of contact for each child in the country (a provision which has not been universally welcomed), it is the sections of the Act that have implications for 'looked after' children in particular that will be of most interest to readers of the Journal.